A Failed Upheaval? - Duncan Henderson (Groundings, 2022)
Opposition to the adversarial politics of the Westerminster Parliament was closely interwoven with the campaign for Scottish devolution. Upon its foundation, the initial proponents of Scottish devolution intended for the new Scottish Parliament to embrace a more consensual ‘new politics’. Evaluating the success of these aspirations through the framework of the Consultative Steering Group’s principles of power-sharing, accountability, access and participation, and equal opportunities, this essay argues that the Scottish Parliament has not delivered the ‘new politics’ expected upon its foundation.